REKONSTRUKSI PEKAN TIGA LINGGA, SUMATERA UTARA ABAD KE-19 (Studi Etnoarkeologi) - - Arunagren; Widya Nayati (Balai Arkeologi Sumatera Utara, 2019)
Tiga Lingga is refers to marketplace which located in the hinterland of North Sumatera. Toponym of Tiga refers to pharse in Tamil Language, katika-t-tavalam, which means market or pekan. This place become market for hinterland comodities in 19th centuries in Kenegerian Lingga teritory. This research examines the trading activities of Tiga Lingga market in 19th century with ethnoarchaeology approach. This approach is used for answering system behind a symtom archaeological culture using ethnographic data for comparison. Tiga Lingga market it’s aspects in economic activity is used as comparison subject. Subjects were analyzed using analysis of cultural continuity for used to awnser the paradigm of archaeological science that reconstruct activity in the past. This reserch concludes that the trading activity of Tiga Lingga market have the same similarities with Tiga Lingga market trading activity in the 19th century. It can be proved from the marketplace, day, time market and some economic aspects that does not change. For conclusions, Tiga Lingga was an old market at least in 19th century, which trading activity is still survive.